Assessment of the capacity to create and understand wordbuilding structures by a child with minor intellectual disability - Mateusz Szurek, Mateusz Szurek (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
The research conducted on language of children with intellectual disability (ID) shows that they exhibit language dysfunctions on every level of language. Up to now, literature did not include linguistic studies concerning issues of wordbuilding in the language consciousness of pre-school children with intellectual disability. The objective of the article is the assessment of the level of wordbuilding competences of a child at pre-school age with minor intellectual disability (MID) concerning the creation and comprehension of nominal derivates in the area of selected wordbuildin categories (case study). In addition, the author wishes to stress that the assessment of the level of wordbuilding competences should be a component on comprehensive logopaedic diagnosis.